S59 Do 'pneumothorax-only' mutations of FLCN really exist?. (December 2018) - Matsumoto, K; Maher, E; Marciniak, SJ
Abstract : Introduction: Birt-Hogg-Dubé (BHD) syndrome is an autosomal dominant disorder caused by mutations of FLCN . Individuals with BHD typically develop facial fibrofolliculomas, pneumothorax and/or renal cell carcinoma (RCC). Pneumothoraces in BHD mostly occur before the age of 40 years, while the mean age of RCC is 50 years. This offers the opportunity to diagnose BHD before RCC has occurred. When identified early, RCC is frequently curable making renal surveillance valuable in BHD. It has been suggested that some mutations of FLCN cause only pneumothorax. If so, these patients would not require renal surveillance. Objective: We set out to define the genotype-phenotype correlation for FLCN mutations and thus determine if 'pneumothorax-only' mutations really exist. Methodology: PubMed was searched for 'Birt-Hogg-Dubé OR Hornstein-Knickenberg'; only studies identifying FLCN mutations were retained (mutation was defined according to ClinVar or LOVD genetic databases or the American College of Medical Genetics and Genomics guidelines). Results: In this way, 765 individuals were identified with 144 unique mutations: 51 were reported with both pneumothorax and RCC (not necessarily the same individuals), 50 only with pneumothorax, 15 only with RCC, 20 with neither pneumothorax nor RCC, and the remaining 8 mutations could not be classified. Analysis of gene structure revealed no preferred locations for pneumothorax-only or RCC-only mutations. When mapped onto the structure of folliculin's C-terminal domain, there was no preferential clustering of pneumothorax-only or RCC-only mutations (figure 1). The majority of pneumothorax-only or RCC-only mutations affected fewer than three individuals each. Analysis of the ages of individuals with pneumothorax-only mutations revealed them to be a significantly younger population compared with individuals with mutations reported to cause RCC (Mann-Whitney U test, p<0.05). Conclusion: No bias was identified in the locations of mutations reported to cause only pneumothorax. Individuals with pneumothorax-only mutations were significantly younger than other patients with BHD. Large deletions and truncating mutations are common in both typical and 'pneumothorax-only' BHD suggesting that folliculin loss-of-function explains the pathogenesis in both instances. These observations suggest that pneumothorax-only FLCN mutations likely reflect ascertainment bias. We recommend that all patients with a FLCN mutations should be offered renal surveillance.